Integration Approaches in Forensic Portrait Examination - N. N. Ilyin (Теория и практика судебной экспертизы, 2024)
The article reviews some actual issues of the theory and practice of the production of forensic portrait examinations: the tight deadlines of the preliminary investigation, the increased time expenditures to produce forensic video examination, the need for an integrated approach to the training of forensic portrait experts. The author proposes to revise some approaches to the training of forensic experts in the field of forensic portrait examinations. Along with the possibility of a comprehensive forensic examination, taking into consideration current needs of practice, more attention needs to be paid to software application for processing photo and video images processing in order to improve visual perception of the information displayed and to study montage marks and their detectability. All this will contribute to the evolvement of a portrait examiner as a specialist of double competence.